Capital Structure: Capital Buffer, Return on Equity, Capital Adequacy Ratio in Go-Public Banking in Indonesia - Muhammad Wahyudin; Marlina Widiyanti; Isni Andriana; Isnurhadi Isnurhadi (Journal of Social Science)
Banking companies may be faced with adjustment costs (cost of capital adjustment) to obtain optimal capital ratios. These costs arise when banks increase or obtain new external capital so that capital adjustments can lead to excess or shortage of capital which can have a negative impact and cause banks to be reluctant to react quickly when capital shocks occur. This research explores the most significant factors that influence bank capital policy choices in Indonesia. This study examines the financing choices of 8 banks for the 2013-2022 period using panel data regression analysis techniques with STATA.17. The results of the Random Effect Model Estimation research where bank companies in Indonesia have high leverage support the fact that the nature of bank business is different from non-banking companies. The significant negative relationship of the capital buffer is in line with the too big fail theory, packing order theory and agency theory, as well as the Retrun On Equity and Capital Adequancy Ratio variables which have a significant positive relationship at an accuracy level of 85.01%, so in other words banking companies can use debt to finance the company on the basis of agency or managerial policies and strategies, thereby proposing pecking order theory with the assumption that there is information asymmetry and agency costs that are relevant both in the long term.